2019
DOI: 10.1186/s12891-019-2426-2
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pains and cardiovascular autonomic function in the general Northern Finnish population

Abstract: BackgroundHeart rate variability (HRV) and baroreflex sensitivity (BRS) measurements provide means for the objective assessment of cardiovascular autonomic function. As previous studies have associated chronic pain with abnormal autonomic function, we aimed to characterize the relationship between the number of musculoskeletal pain sites (NPS), pain intensity, and cardiovascular autonomic function among the population-based Northern Finland Birth Cohort 1966.MethodsAt the age of 46, cohort members self-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In our data, the discordance between the results drawn from the crude and adjusted models suggests that the association between LBP, sciatica and cardiovascular autonomic function is greatly confounded and/or mediated by external factors such as sex, BMI, LTPA, smoking status, other musculoskeletal pains, somatic and psychiatric comorbidity and ANS-related medication. Two previous papers have obtained similar findings 24,25 . Thus, in order to reveal the independent association between pain and ANS function, future studies should aim to record these background characteristics at the data collection stage, and use these variables to control for the potential confounder effects.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In our data, the discordance between the results drawn from the crude and adjusted models suggests that the association between LBP, sciatica and cardiovascular autonomic function is greatly confounded and/or mediated by external factors such as sex, BMI, LTPA, smoking status, other musculoskeletal pains, somatic and psychiatric comorbidity and ANS-related medication. Two previous papers have obtained similar findings 24,25 . Thus, in order to reveal the independent association between pain and ANS function, future studies should aim to record these background characteristics at the data collection stage, and use these variables to control for the potential confounder effects.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, another recent meta-analysis found a consistent, moderate-to-large effect of decreased HRV in chronic pain, suggesting a decrease in parasympathetic activation in individuals with pain 14 . In light of several smaller studies, this association seems to also concern LBP and sciatica 12,13,21,22 , although previous studies have reported the association between musculoskeletal pain and ANS function to be potentially confounded by lifestyle factors and/or comorbidities 24,25 . The present study aimed to supplement the previous investigations of LBP, sciatica and cardiovascular autonomic function by constructing 15-year pain trajectories to be assessed against both HRV and BRS parameters in a general population sample.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Musculoskeletal disorders comprise of a wide range of diseases and conditions, most common include tendonitis, osteoarthritis and rheumatoid arthritis. While some studies report a negative association between osteoarthritis (a musculoskeletal disorder) and hypertension [28,29]; others report a positive association between hypertension and musculoskeletal complaints, like rheumatoid arthritis and musculoskeletal pain [30][31][32]. These studies suggest that musculoskeletal pain affect the Autonomic Nervous System (ANS) that controls the cardiovascular activities and regulates blood pressure levels and heart rate, and this might interfere with both diastolic and systolic blood pressure levels [31].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…While some studies report a negative association between osteoarthritis (a musculoskeletal disorder) and hypertension [28,29]; others report a positive association between hypertension and musculoskeletal complaints, like rheumatoid arthritis and musculoskeletal pain [30][31][32]. These studies suggest that musculoskeletal pain affect the Autonomic Nervous System (ANS) that controls the cardiovascular activities and regulates blood pressure levels and heart rate, and this might interfere with both diastolic and systolic blood pressure levels [31]. On the other hand, diabetes mellitus and hypertension are stated to have bi-directional relationship with shared risk factors.…”
Section: Plos Global Public Healthmentioning
confidence: 99%